Pengaruh jumlah uang beredar, suku bunga, dan inflasi terhadap pertumbuhan ekonomi di Indonesia tahun 2012–2024 ditinjau dalam perspektif ekonomi Islam - Sinta Tri Utami; Muhammad Iqbal; M. Yusuf Bahtiar (AL-Muqayyad, 2026)
This study aims to analyze the influence of money supply, interest rates, and inflation on economic growth in Indonesia for the 2012-2024 period using the VECM with quarterly data of 52 observations. The cointegration test results indicate a long-term relationship among the variables. In the long run, inflation has a significant effect on GDP, while money supply has a negative but very small effect, and interest rates have no significant effect. Overall, the three monetary variables collectively contribute less than 1% to GDP variations, thus they are not the main factors driving economic growth. The policy implications of these findings include the need to prioritize inflation control and reevaluate the effectiveness of interest rate instruments and money supply expansion in promoting growth. The contribution of this research lies in using a study period that covers various economic shocks (taper tantrum, pandemic, and recovery) and applying the VECM method capable of separating short-run and long-run effects. From the perspective of Islamic economics, these findings support the principles of distributive justice and the prohibition of usury (riba), as interest-based instruments prove ineffective, making the development of Sharia-based monetary policy through profit-sharing schemes a more relevant and equitable alternative.